2021
DOI: 10.3390/land10101087
|View full text |Cite
|
Sign up to set email alerts
|

Four Years Continuous Monitoring Reveals Different Effects of Urban Constructed Wetlands on Bats

Abstract: Proactive artificial wetland constructions have been implemented to mitigate the loss of wetlands and their ecosystem services. As wetlands are habitats for bats, short-term (one or two years) studies find that constructed wetlands can immediately increase local bat activity and diversity. However, it is not clear how constructed wetlands affect bats through time while the wetlands are aging. We collected four years of continuous bat acoustic monitoring data at two constructed wetlands in an urban park in Gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 77 publications
(130 reference statements)
0
7
0
Order By: Relevance
“…One aspect that our study was not able to address was how interspecific or intraspecific interactions among bats might affect species’ responses to ALAN. When optimal prey sources are available, bats might compete to dominate the prey source [ 81 , 82 , 83 , 84 ]. All species we examined were either open or edge foragers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One aspect that our study was not able to address was how interspecific or intraspecific interactions among bats might affect species’ responses to ALAN. When optimal prey sources are available, bats might compete to dominate the prey source [ 81 , 82 , 83 , 84 ]. All species we examined were either open or edge foragers.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the evening bat was the only species in our study that showed no response to ALAN or spatial complexity. Considering this species is generally smaller than other species in the study area [ 55 ] and has been found less competitive with other species [ 81 , 82 ], we suspected that evening bat foraging activity might be opportunistic. Further study should address possible bat community dynamics under ALAN in relation to prey availability.…”
Section: Discussionmentioning
confidence: 99%
“…Our study design allowed discrimination between the expected spatial and temporal variation in bat presence and activity, and the effect of the restoration actions. Flaquer et al 2009;Maslonek 2010;Ciechanowski et al 2011;Stahlschmidt et al 2012;Korine et al 2015;Straka et al 2016;Parker et al 2019;Toffoli & Rughetti 2020;Beranek et al 2021;Li et al 2021), while one study investigated the effects of drainage (red diamonds; Vindigni et al 2009).…”
Section: Sampling Designmentioning
confidence: 99%
“…1). High bat activity has also been recorded at these sites, showing that they could also have an important role in bat conservation (Beranek et al 2021; Li et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Oligochaetes, nematodes, ostracods, and chironomids were the most common taxa found [244]. Over time, artificial wetlands stop attracting different species of bats [245,246]. When assessing mosquito risk, they should not be considered collectively, as that does not reveal links with urban wetland habitats or measures of aquatic diversity.…”
Section: Regulation Services: Biodiversitymentioning
confidence: 99%